Immediate Bilateral Breast Reconstruction with Unilateral Deep Superior Epigastric Artery and Superficial Circumflex Iliac Artery Flaps - Hansen, Keith S.; Gutwein, Luke G.; Hartman, Brett C.; Sood, Rajiv; Socas, Juan (Archives of Plastic Surgery, 2016)
Autologous breast reconstruction utilizing a perforator flap is an increasingly popular method for reducing donor site morbidity and implant-related complications. However, aberrant anatomy not readily visible on computed tomography angiography is a rare albeit real risk when undergoing perforator flap reconstruction. We present an operative case of a patient who successfully underwent a bilateral breast reconstruction sourced from a unilateral abdominal flap divided into deep superior epigastric artery and superficial circumflex iliac artery flap segments.
Keywords: Breast; Microsurgery; Reconstructive surgical procedures